French Decorative Ceramics Mass‐Produced During and After the 17th Century: Chemical Analyses of the Glazes. (14th March 2018) - Bouquillon, A.; Castaing, J.; Barbe, F.; Crepin‐Leblond, T.; Tilliard, L.; Paine, S. R.; Christman, B.; Heuer, A. H.
Abstract : Chemical analyses of a group of Pb silicate–glazed decorative objets d'art showing scenes of the French royal family (Louis XIII and Henri IV), and biblical and classical figures, have been analysed and compared with other similar heritage ceramics and with the rustiques figulines of Bernard Palissy (1510–90) and his followers and imitators. In particular, non‐destructive ion‐beam chemical analyses (PIXE and PIGE) have been performed on 11 ceramic artefacts from the Cleveland Museum of Art (CMA) and a like number from several French museums; results for 13 objects are described in detail in this paper. SEM–EDX has been performed on chips ('microsamples') taken from small unobtrusive defective regions on the CMA ceramics. The results of the ion‐beam and SEM–EDX techniques are in good agreement. All the decorative ceramics included uniform non‐opacified glazes. None of these objects can be of 16th century production; all must date from the 17th to the 19th centuries.